Here's the question you clicked on:
I<3Fun
Solve the following equation. One point is given for showing steps and one point given for the correct solution. (5x - 1)/2 + (-3x - 1)/4 = 9/2
2(5x-1) + (-3x - 1) = (4)(9/2) 10x - 1 + 3x - 1 = 36/2 13x - 2 = 18 13x = 20 x = 20/13
2(5x-1) + (-3x - 1) = (4)(9/2) 10x - 2 + 3x - 1 = 36/2 13x - 3 = 18 13x = 21 x = 21/13
lol heyyy haha and omg M!!!! LOL
(5x-1)2 + (-3x - 1)/4 =9/2 I would multiply all terms by 4 2(5x-1) +(-3x - 1) =18 remove parens 10x-2-3x-1=18 Now consolidate similar terms. 7x-3=18 add 3 to both sides 7x=21 x= 3 dividing both sides by 7
nm my dad is setting up a new computer for me and im finishing up my hm :P
learn from my common mistakes :)
alrighty!! thanks guys wow those are like not the steps i was using ^^ and yea i do that all the time dont worry!
i did all my other problems and now im doing the ones that i couldnt do >.< prolly gonna be posting like a few more questions ^^